Correlation between follicular fluid hormonal levels in PCOS women and embryo development in ART cycles - Sunatchana Kongsomnuan; Pornsri Niransuk; Artitaya Singwongsa; Chonthicha Satirapod (PLoS ONE, 2026)
Polycystic ovarian syndrome (PCOS) is a common endocrine disorder characterized by ovulatory dysfunction. Fertility outcomes in PCOS patients are often suboptimal, potentially owing to alterations in the follicular fluid (FF) microenvironment. However, the differences in FF hormone levels between PCOS and non-PCOS patients, as well as their correlation with assisted reproductive technology (ART) outcomes, remain unclear. This prospective study included 18 PCOS patients and 18 infertile women without PCOS (control group) undergoing intracytoplasmic sperm injection at the Division of Reproductive Medicine, Ramathibodi Hospital. The primary objective was to compare ART outcomes between the groups. Furthermore, FF testosterone, dehydroepiandrosterone sulfate, and luteinizing hormone levels were evaluated to assess their correlation with these outcomes. The number of retrieved oocytes was significantly higher in the PCOS group; however, the rates of metaphase II oocyte formation, fertilization, blastocyst formation, and high-quality blastocyst formation were comparable between the groups. Although FF testosterone and FF luteinizing hormone levels were higher in the PCOS group than in the control group, the differences were not statistically significant. Spearman correlation analysis showed that FF testosterone levels were negatively correlated with fertilization rate (r = −0.3496, p = 0.0366). These findings suggest that increased FF testosterone levels may negatively correlation with fertilization rates, which may reflect one of the contributing factors to the suboptimal ART outcomes observed in PCOS patients.